2020
DOI: 10.1590/2317-1545v42236272
|View full text |Cite
|
Sign up to set email alerts
|

Does nitric oxide protect Eucalyptus urophylla seeds under salt stress conditions?

Abstract: The germination response of seeds under artificial stress conditions is a tool for better understanding of the survival and adaptation ability of species under natural stress conditions. The aims of this study were to evaluate the protective effect of nitric oxide during germination as well as seed vigor and seedling development of Eucalyptus urophylla under salt stress conditions. The experimental design was completely randomized, with five replications, in a 3 × 3 + 1 factorial arrangement, with three primin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Salt inhibits seed germination, thereby causing great damage to agricultural production. Several reports have shown that the application of SNP under saline conditions increases the percent germination of various plant species, including Eucalyptus urophylla , wheat, and rice [ 30 , 31 , 32 ]. Another study found that NO alleviated the decreases in germination percentage, germination index, vigor index, and imbibition rate of wheat seeds exposed to salt stress, mainly by increasing beta-amylase activity [ 31 ].…”
Section: No Alleviates Salt Stress-induced Damagementioning
confidence: 99%
“…Salt inhibits seed germination, thereby causing great damage to agricultural production. Several reports have shown that the application of SNP under saline conditions increases the percent germination of various plant species, including Eucalyptus urophylla , wheat, and rice [ 30 , 31 , 32 ]. Another study found that NO alleviated the decreases in germination percentage, germination index, vigor index, and imbibition rate of wheat seeds exposed to salt stress, mainly by increasing beta-amylase activity [ 31 ].…”
Section: No Alleviates Salt Stress-induced Damagementioning
confidence: 99%
“…The information on the impact of NO on plants can sometimes be contradictory, because the effects depend on the plant species and seedling age, as well as the duration, and severity of the abiotic stress [ 31 , 33 , 44 ]. The application of the exogenous NO donor sodium nitroprusside (SNP), has been shown to cause a promising effect on crop germination under control conditions and NaCl-induced stress, as well as on fresh weight, dry weight, and shoot and root elongation [ 5 , 45 , 46 , 47 , 48 , 49 ]. It has also been shown that NO alleviates oxidative damage (i.e., decreased electrolyte leakage and lipid peroxidation) by increasing antioxidant activities [ 29 , 48 ] and preventing changes in thylakoid shape and size [ 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…NO has a positive effect on several plant cellular procedures, including: Breaking seed dormancy, growth and plant defense against stress. It can even has an effect on abscisic acid expression in dormancy breaking, acting positively on germination (Silva et al, 2019;Pereira et al, 2020).…”
Section: Introductionmentioning
confidence: 99%